The use of barocaloric effect for energy saving in a domestic refrigerator with ethylene-glycol based nanofluids: A numerical analysis and a comparison with a vapor compression cooler. (1st January 2020) - Aprea, C.; Greco, A.; Maiorino, A.; Masselli, C.
Abstract: This paper focuses on barocaloric refrigeration that could represent a practicable environmentally friendly alternative to vapor compression. The energy performances of an active barocaloric refrigerator working as a domestic cooler are evaluated by means of a 2-Dimensional model, already validated in previous investigations. The energy performances are also compared with experimental data referred to a household vapor compression refrigerator working with HFC134a. The active barocaloric regenerative refrigeration cycle is supposed to work as a domestic refrigerator in temperature range of 255 ÷ 290 K. The heat-transfer fluid is a mixture of 50%ethylene-glycol-50%water, whereas acetoxy silicone rubber is the solid-state refrigerant. In order to enhance the energy performances of the solid-state refrigerator the use of Cu-based nanofluids in the anti-freezing mixture was tested. The addition of Cu-nanoparticles to the 50%ethylene-glycol- 50%water mixture ensures a moderate enhancement of the energy performances (the maximum temperature span, cooling power and coefficient of performance enhancements are +4.0%, +7.3% and +6.7%, respectively). The analysis shows that barocaloric refrigeration can be a promising new technology in the field of domestic refrigeration for energy saving because it always overperforms vapor compression. Highlights: The energy performances of a barocaloric cooler were evaluated. The heat transfer fluid of the regenerator was a water/glycol ethylene mixture. To enhance the performances the addition of Cu-based nanofluids was tested. A comparison with the data of a R134a vapor compression cooler was done. Barocaloric can be a promising new technology for domestic refrigeration.